Home-based virtual reality-enhanced upper limb training system in children with brain injury: a randomized controlled trial - Choi, Ja Young; Yi, Sook-hee; Shim, Dain; Yoo, Beomki; Park, Eun Sook; Rha, Dong-wook (Frontiers in Pediatrics, 2023)
Background: Rehabilitation of upper limb function can be challenging in children with brain lesion. Recent virtual reality (VR) rehabilitation may be an additional treatment option in pediatric rehabilitation. Objectives: To assess the feasibility and effectiveness of a home-based VR-enhanced rehabilitation program with wearable multi-inertial measurement unit (IMU) sensors on upper limb functions in children with brain injury. Methods: This multicenter single blind randomized controlled trial included 40 children with cerebral palsy (CP) or static brain injury. Subjects were randomized 1:1 to experimental and control group. Both the groups maintained the same therapeutic content and dose of occupational therapy during the intervention period. The experimental group performed additional training at home using the VR-enhanced program for at least 30 min/day, 5 days/week, for 6 weeks. VR training consisted of daily activities or games promoting wrist and forearm articular movements using wearable IMU sensors. The Melbourne Assessment of Unilateral Upper Limb Function-version 2 (MA2), Upper Limb Physician’s Rating Scale (ULPRS), Pediatric Evaluation of Disability Inventory-computer adaptive test (PEDI-CAT), computerized 3D motion analysis, and user satisfaction survey were performed. Mann–Whitney U test was used to compare treatment effects between groups, and Friedman and Wilcoxon signed-rank tests were used to compare pre and post intervention. Results: Overall 35 children (15 in VR group and 20 in control group) completed the protocol. In the experimental group, an average VR training time was 855 min. The accuracy of motion measured by MA2, segmental movements by ULPRS, daily living capability and social cognitive function by PEDI-CAT, movement time and shoulder movement pattern by motion analysis showed significant improvements. However, there were no significant differences in any of the functional outcome measures compared to the control group. All the children and parents reported positive experiences. Conclusions: Home-based VR training though it had limited impact on improving upper limb function, it could help improve social cognitive function, movement pattern, and efficiency in children with brain injury and could be an effective means of extending clinical therapy to the home. CRIS.nih.go.kr: KCT0003172